ANALISIS PENGARUH BAURAN PEMASARAN TERHADAP MINAT BELI BUAH-BUAHAN PADA UMKM BUAH BARU ONLINE: Buah : Minat Beli; Online - Rahmawati Setiyani; Edi Waluyo, Sugeng; Agidya Putra, Rajendra (FAKULTAS PERTANIAN UNIVERSITAS SLAMET RIYADI, 2024)
The development of digital technology has touched various sectors in Indonesia. The presence of an oline market can help entrepreneurs market their products. MSMEs Buah Baru Online operates in the online fruit sales sector. The hope is that the business carried out by connecting consumer via the internet can increase fruit sales. However, there is a problem that the marketing mix implemented by MSMEs Buah Baru Online is not optimal. The aim of this reserach is to analyze the influence of the marketing mix on interest in buying fruit online among MSMEs Buah Baru Online. The basic method in this reserach is descriptive analysis. Data analysis uses multiple linear regression analysis to determine ter influence of the independent variables, namely Product (X1), Price (X2), Place (X3), Promotion (X4) as well as the dependent variable, namely Purchase Interest (Y). Consumer characteristics of MSMEs Buah Baru Online are dominated by female aged 35 until 44 years old with occupation as employee and income more than IDR 3.000.001,00. The marketing mix together influences the interest in buying fruit online among MSMEs Buah Baru Online. The better marketing mix that is implemented the more it can increase consumer buying interest in the MSMEs Buah Baru Online.